Constraints Faced by the Practicing Farmers in Adoption of Zero Tillage Technology in Punjab - Devinder Tiwari, Manjit Kaur; R K Dhaliwal (Indian Journal of Extension Education, 2022)
The present study was undertaken to know the constraints faced by the farmers in adoption of Zero Tillage Technology. A sample of 180 practising farmers was randomly selected from the six purposively selected districts of the State. The data were collected personally with the help of an interview schedule. The findings of the study reveal that loose straw left behind in the paddy harvested fields and its management was the major technical constraint faced by majority of the respondents. Lack of training on ZTT to meet the informaton needs was observed as the most serious training and educational constraint followed by availability of adequate extension literature about ZTT. Among the financial constraints, lack of adequate financial incentives by way of insurance of the crop sown with Zero Tillage Technology and availing of subsidy only by high profile farmers was reported as the major constraints by 20-28 per cent of the respondents. Among the psychological constraints, the look of the field before and after the sowing by ZTT was reported as constraint by the majority of the respondents.